2004
DOI: 10.1111/j.1600-6143.2004.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation from Donors Aged 80 Years and Over: Pushing the Limit

Abstract: Older donors are a growing part of the total donor pool but no definite consensus exists on the limit of age for their acceptance. From November 1998 to January 2003, in a retrospective case-control multicenter study, we compared the outcome of 30 orthotopic liver transplantations (OLTs) with octogenarian donors and of 60 chronologically correlated OLTs performed with donors <40 years. The percentage of refusal was greater among older than younger donors (48.2 vs. 14.3%; p < 0.001). Cold ischemia was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
3
34

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 28 publications
7
112
3
34
Order By: Relevance
“…This finding raises the question as to whether organs of aged donors, who would be considered unacceptable for most LT recipients, may in fact provide adequate liver function for these ALD patients. Some centres have published excellent results for donor organs up to the age of 80 years and more [19][20][21][22][23]. However, we know that organs from older donors are more susceptible to ischemia-reperfusion injury, and these grafts do worse in patients with high MELD scores [24][25][26].…”
Section: Discussionmentioning
confidence: 97%
“…This finding raises the question as to whether organs of aged donors, who would be considered unacceptable for most LT recipients, may in fact provide adequate liver function for these ALD patients. Some centres have published excellent results for donor organs up to the age of 80 years and more [19][20][21][22][23]. However, we know that organs from older donors are more susceptible to ischemia-reperfusion injury, and these grafts do worse in patients with high MELD scores [24][25][26].…”
Section: Discussionmentioning
confidence: 97%
“…In a retrospective review of 111 patients transplanted for hepatitis C related CLD, Rayhill et al [11] reported that grafts from donors over 60 years of age were associated with severe recurrent HCV. Several authors have suggested that these should be avoided in HCV recipients [12,13] . Despite these issues, older donors remain a valuable source of organs [14][15][16] .…”
Section: Agementioning
confidence: 99%
“…More recent reports analyzing large transplant registries have confirmed the animal models [1,2], livers from older donors do not seem to recover from damage as rapidly or completely as those from younger donors. Nonetheless, there are also many smaller studies reporting excellent results using liver grafts from donors in their 70s [3,4] or even in selected donors greater than 80 years old [5,6]. These results with older donors highlight the fact that both donor and recipient factors contribute to long-term results and that utilizing organs from older donors must be weighed in the context of all the risks candidates face waiting.…”
Section: Donor Agementioning
confidence: 94%